2021
DOI: 10.3390/molecules26164720
|View full text |Cite
|
Sign up to set email alerts
|

Co-Treatment of Purified Annatto Oil (Bixa orellana L.) and Its Granules (Chronic®) Improves the Blood Lipid Profile and Bone Protective Effects of Testosterone in the Orchiectomy-Induced Osteoporosis in Wistar Rats

Abstract: This study aimed to evaluate and compare the effects of co-treatment with purified annatto oil (PAO) or its granules (GRA, Chronic®) with that of testosterone on the orchiectomy-induced osteoporosis in Wistar rats. After surgery, rats were treated from day 7 until day 45 with testosterone only (TES, 7 mg/kg, IM) or TES + PAO or GRA (200 mg/kg, p.o.). The following parameters were evaluated: food/water intake, weight, HDL, LDL, glucose, triglycerides (TG), total cholesterol (TC), alkaline phosphatase levels, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The animals were randomly divided into seven groups (n = 8 per group) and treated orally for 40 days: (1) treated with 0.5 mL of distilled water and 2 mL/day (GSC); (2) treated with vehicle 5% lecithin (VEI); (3) treated with simvastatin 20 mg/kg (SIN); (4) treated with 200 mg/kg of granules (CHR); (5) treated with 200 mg/kg (OFEO); (6) treated with 200 mg/kg (OFAE); (7) treated with 200 mg/kg (OFBO). The study carried out was based on the doses of previous works, thus substantiating the applied methodology [ 104 ].…”
Section: Methodsmentioning
confidence: 98%
“…The animals were randomly divided into seven groups (n = 8 per group) and treated orally for 40 days: (1) treated with 0.5 mL of distilled water and 2 mL/day (GSC); (2) treated with vehicle 5% lecithin (VEI); (3) treated with simvastatin 20 mg/kg (SIN); (4) treated with 200 mg/kg of granules (CHR); (5) treated with 200 mg/kg (OFEO); (6) treated with 200 mg/kg (OFAE); (7) treated with 200 mg/kg (OFBO). The study carried out was based on the doses of previous works, thus substantiating the applied methodology [ 104 ].…”
Section: Methodsmentioning
confidence: 98%
“…Considering the role of this enzyme in cholesterol biosynthesis, this could be a mechanism in which geranylgeraniol exerts its action. Our group reported that the treatment with geranylgeraniol improved blood lipid parameters; however, the molecule was not administrated alone but with tocotrienols [8]. Altogether, the in silico prediction with its known mechanism of action justifies future studies with this molecule alone in treating blood dyslipidemia in vivo.…”
Section: Molecules' Structure Obtention and Biological Activity Predi...mentioning
confidence: 96%
“…It is believed that one of the main targets for the hypocholesterolemic activity of tocotrienols is HMG-CoA reductase. This enzyme catalyzes the rate-limiting step in cholesterol biosynthesis [31] and is also targeted by statins, although these molecules inhibit its activity in a different way [8]. As mentioned, there are some reports of HMGR inhibition by geranylgeraniol as well.…”
Section: Molecular Dockingmentioning
confidence: 99%
See 2 more Smart Citations